Climate-Smart Agriculture in Peru - Baca, María; Nowak, Andreea C.; Lizarazo, Miguel; Imbach, Pablo; Halliday, Andrew; Zavariz-Romero, Beatriz; Prasodjo, Rauf; Medellín, Claudia; Argote, Karolina; Cervantes De Blois, Chelsea; Zamora, Juan Carlos; Louman, Bastian; et al. (World Bank, 2014)
The climate-smart agriculture (CSA) concept reflects an ambition to improve the integration of agriculture development and climate responsiveness. It aims to achieve food security and broader development goals under a changing climate and increasing food demand.